Cultural adaptation and psychometric assessment of the Persian version of the lumbar spine instability questionnaire - Noureddin Nakhostin Ansari; Zahra Abdollahzade; Soofia Naghdi; Mohammad Taghi Beigmohammadi; Mina Kashi-Alashti (BMC, 2022)
Abstract Background The Lumbar Spine Instability Questionnaire (LSIQ) is a self-reported measure of clinical instability of the lumbar spine. This study aimed to translate and culturally adapt the LSIQ into Persian language (LSIQ-P) and to evaluate its reliability and validity in a sample of patients with chronic non-specific low back pain (LBP). Methods In a cross-sectional study, the LSIQ was translated using guidelines. Participants with chronic non-specific LBP, aged ≥ 18 years old, answered an online survey consisting of LSIQ-P, the Persian Functional Rating Index (FRI), and the pain Numeric Rating Scale (NRS). Construct validity, internal consistency reliability, test-retest reliability, standard error of measurement (SEM), smallest detectable change (SDC), discriminant validity, and factor analysis were evaluated. Results The LSIQ was successfully adapted into Persian. A sample of 100 participants with LBP and 100 healthy subjects completed the survey. Floor and ceiling effects were not observed. Cronbach's alpha = 0.767 and ICCagreement = 0.78 indicated good internal consistency and test-retest reliability. The SEM and SDC were 1.53 and 4.24, respectively. Construct validity of LSIQ-P was confirmed with significant correlation with Persian FRI (r = 0.44, p < 0.001) and pain NRS (r = 0.30, p = 0.003). An evidence of discriminant validity was demonstrated by significant difference in LSIQ-P total scores between the patients with LBP and healthy subjects, and between the patients with high total score ≥ 9 and those with low total score < 9 on the LSIQ-P. The LSIQ-P was found a multidimensional instrument with eight items appeared being redundant. Conclusions The Persian LSIQ showed satisfactory metric characteristics of reliability and validity. Further studies are required to elucidate the internal structure of the LSIQ-P.